Integrated analysis of genome‐wide copy number alterations and gene expression in microsatellite stable, CpG island methylator phenotype‐negative colon cancer. Issue 5 (23rd January 2013) - Loo, Lenora W. M.; Tiirikainen, Maarit; Cheng, Iona; Lum‐Jones, Annette; Seifried, Ann; Church, James M.; Gryfe, Robert; Weisenberger, Daniel J.; Lindor, Noralane M.; Gallinger, Steven; Haile, Robert W.; Duggan, David J.; et al.
Abstract Microsatellite stable (MSS), CpG island methylator phenotype (CIMP)‐negative colorectal tumors, the most prevalent molecular subtype of colorectal cancer, are associated with extensive copy number alteration (CNA) events and aneuploidy. We report on the identification of characteristic recurrent CNA (with frequency >25%) events and associated gene expression profiles for a total of 40 paired tumor and adjacent normal colon tissues using genome‐wide microarrays. We observed recurrent CNAs, namely gains at 1q, 7p, 7q, 8p12‐11, 8q, 12p13, 13q, 20p, 20q, Xp, and Xq and losses at 1p36, 1p31, 1p21, 4p15‐12, 4q12‐35, 5q21‐22, 6q26, 8p, 14q, 15q11‐12, 17p, 18p, 18q, 21q21‐22, and 22q. Within these genomic regions we identified 356 genes with significant differential expression (P < 0.0001 and ±1.5‐fold change) in the tumor compared to adjacent normal tissue. Gene ontology and pathway analyses indicated that many of these genes were involved in functional mechanisms that regulate cell cycle, cell death, and metabolism. An amplicon present in >70% of the tumor samples at 20q11‐20q13 contained several cancer‐related genes (AHCY, POFUT1, RPN2, TH1L, and PRPF6) that were upregulated and demonstrated a significant linear correlation (P < 0.05) for gene dosage and gene expression. Copy number loss at 8p, a CNA associated with adenocarcinoma and poor prognosis, was observed in >50% of the tumor samples and demonstrated a significant linear correlation for gene dosage and gene expression for two potential tumor suppressor genes, MTUS1 (8p22) and PPP2CB (8p12). The results from our integration analysis illustrate the complex relationship between genomic alterations and gene expression in colon cancer. © 2013 Wiley Periodicals, Inc.